Employing IT Service Management to Accelerate Digital Government Transformation in Saudi Arabia: A Vision 2030 Perspective - Abudaqqa, Fatma (European Scientific Journal, ESJ, 2025)
Saudi Arabia’s Vision 2030 prioritizes digital transformation as a driver of efficient, citizen-centered governance, with Information Technology Service Management (ITSM) positioned as a critical enabler. This study assessed how ITSM maturity influences digital service performance and contributes to national transformation goals. A sequential explanatory mixed-methods design was applied, including an online survey of 80 IT managers from ministries, municipalities, and utilities, 15 semi-structured interviews with senior IT leaders, and a case study of the Ministry of Interior’s Absher platform. Survey data were analyzed using descriptive statistics, Pearson correlations, and linear regression; qualitative data were coded thematically. Results showed that agencies with higher ITSM maturity achieved significantly greater system uptime (r = 0.53, p < .01) and citizen satisfaction (r = 0.70, p < .01). Regression analysis confirmed that each one-point increase in maturity predicted approximately a 3.3% increase in service uptime and a 0.5-point gain in satisfaction on a five-point scale. Interviews and the Absher case highlighted leadership commitment, structured workforce training, and Vision 2030 alignment as key enablers, while skills shortages, legacy infrastructure, and cultural resistance were persistent barriers. The findings demonstrate that ITSM maturity directly supports the Kingdom’s strategic targets for reliability and user satisfaction. Policymakers and public-sector leaders are encouraged to strengthen governance, invest in skills pipelines, and modernize legacy systems to scale ITSM benefits across agencies and sustain Saudi Arabia’s regional leadership in digital government.